PHENIX: product history-based reverse engineering. (1st January 2013) - Durupt, Alexandre; Remy, Sébastien; Bricogne, Matthieu; Troussier, Nadège
Reverse engineering (RE) is an activity which consists in digitising a real part in order to create a CAD model. Today, a lot of references are centred on geometrical approaches based on transformations of the point cloud. The issued CAD models are generally 'frozen' or barely re-usable. Nevertheless, to support engineering changes in a new design process, the product should be represented with a parametric geometry. This paper suggests a knowledge-based approach in order to provide a product's parametric CAD model. A data model based on the extension of the core product model (CPM) is suggested and enables to manage multi-CAD models of the knowledge-based RE process.